Collocation method for solving singularly perturbed boundary-value problems by using cubic splines - Blatov, I. A.; Pokornaya, I. Yu.; Strygin, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider singularly perturbed boundary-value problems in the case of boundary layers. To find approximate solutions of these problems, we use a collocation method based on cubic splines of minimal defect on nonuniform meshes.